2020
DOI: 10.51703/bm.v2i2.28
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationships among Product Quality, Customer Satisfaction and Loyalty in the Bamboo Institute, Dili, Timor-Leste

Abstract: The objectives of this research are to test and explain the influence of product quality and customer satisfaction on customer loyalty, in addition to customer satisfaction on the relationship between product quality and customer loyalty. A total of 190 valid questionnaires were collected from costumers of Bamboo Institute in Dili, Timor-Leste, and the relationships between 3 variables were tested using SMART-PLS 3.0. The result of the study revealed that product quality and customer satisfaction influence pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 44 publications
5
11
1
10
Order By: Relevance
“…Garvin (1988) as cited by Wang et al (2003) presented eight dimensions to measure product quality such as performance, features, conformance, reliability, durability, serviceability, aesthetics, and customer-perceived quality. Rua et al (2020) measured product quality by using four dimensions adapted from previous empirical studies namely conformance to specification (three items), durability (three items), design innovation and improvement (four items), and brand image (six items). "…”
Section: Product Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Garvin (1988) as cited by Wang et al (2003) presented eight dimensions to measure product quality such as performance, features, conformance, reliability, durability, serviceability, aesthetics, and customer-perceived quality. Rua et al (2020) measured product quality by using four dimensions adapted from previous empirical studies namely conformance to specification (three items), durability (three items), design innovation and improvement (four items), and brand image (six items). "…”
Section: Product Qualitymentioning
confidence: 99%
“…The product quality and brand are important factors for customer's consideration before they decide to purchase a product (Belz & Peattie, 2009;Kotler, 2003:224). Therefore, product quality influence positively and significantly on customer satisfaction (Rua et al, 2020), which then lead to significantly impacts on customers' willingness to buy (Beneke et al, 2013). To this, the hypothesis can be formulated as follow: H2: Product quality positively and significantly influences on the purchasing decision.…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies had been done, the results showed that service quality has a positive and significant impact on customer satisfaction (Keshavarz and Jamshidi, 2018;Saldanha et al, 2018;Flores, Saldanha and Vong, 2020;Borishade et al, 2021) because if customers feel that an organization offers good service quality, then they will be happy and will return to buy the product/ service offered (Khoo, Ha and McGregor, 2017;Rua, Saldanha and Amaral, 2020;Annamdevula and Raja Shekhar Bellamkonda, 2016;Borishade et al, 2021). However, study from Famiyeh, Kwarteng and Asante-Darko, (2018) showed that service quality had partial influenced on customer satisfaction due to the reliability dimension in the service quality is not related to customer satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Semakin bermanfaat produk yang ditawarkan maka semakin puas pelanggan terhadap produk tersebut. 13 Visum et Repertum merupakan luaran/produk dari pelayanan kedokteran forensik dan medikolegal, berbentuk suatu surat keterangan resmi yang dibuat oleh dokter sebagai pengganti barang bukti tindak pidana kekerasan di tubuh korban. 1,14 15 Pengumpulan data dilakukan dengan menggunakan google form langsung ke whatsapp penyidik kepolisian dengan link tertentu.…”
unclassified